PENGARUH METODE JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN PERKALIAN BILANGAN 6-9 DI KELAS V SD: THE EFFECT OF THE JARIMATIKA METHOD ON IMPROVING THE ABILITY OF MULTIPLICATION OF NUMBERS 6-9 IN GRADE V OF ELEMENTARY SCHOOL - Putri Dini Retno Pratiwi; Trisnawati, Nika Fetria; Hidayani; Rusani, Irna (KAMBIK: Journal of Mathematics Education, 2024)
Mathematics is a subject that has a fundamental role in teaching students to think logically, critically, and analytically. This study aims to improve students' numeracy skills through the jarimatika learning method. This method provides a simple and interesting approach by using fingers as a medium to learn the concept of multiplying numbers 6-9. This type of research is a Quasi Experiment dengan Non-Equivalent Pretest-Posttest Design conducted on 25 fifth-grade students of SDN 24 Sorong City. The results of the analysis show that this method improves students' numeracy skills. The average pre-test score was 57.76 which increased to 77.36 in the post-test with a minimum score that was initially 40 increasing to 48 and a maximum score that was initially 64 increasing to 100. In addition, the average N-gain of 0.4515 shows an increase in the moderate category. The results of this study prove that the jarimatika method is effective in improving students' numeracy skills while offering an alternative approach that is interesting, fun, and interactive.